2002
DOI: 10.1034/j.1399-6576.2002.t01-1-460316.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the opioid‐sparing efficacy of diclofenac and ketoprofen for 3 days after knee arthroplasty

Abstract: We conclude that in the first day after knee arthroplasty (13-24 h), ketoprofen exerted an opioid-sparing effect. After day 1 (25-60 h), with the doses used, diclofenac proved to be better than placebo, whereas ketoprofen was not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 13 publications
3
32
0
2
Order By: Relevance
“…The 74 trials in this section are grouped into two categories: systemic analgesia and regional anaesthesia Systemic conventional NSAID [9][10][11] . [11] (diclofenac) fl [11] (ketoprofen) NS [9,10] .…”
Section: Pharmacological Agents and Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…The 74 trials in this section are grouped into two categories: systemic analgesia and regional anaesthesia Systemic conventional NSAID [9][10][11] . [11] (diclofenac) fl [11] (ketoprofen) NS [9,10] .…”
Section: Pharmacological Agents and Techniquesmentioning
confidence: 99%
“…[11] (diclofenac) fl [11] (ketoprofen) NS [9,10] . [9, 10]* fl [11] (ketoprofen and diclofenac) n ⁄ a COX-2-selective inhibitor [12][13][14][15] . [12][13][14][15] .…”
Section: Pharmacological Agents and Techniquesmentioning
confidence: 99%
“…A placebo-controlled study comparing the analgesic efficacy of ketoprofen and diclophenac and their effects on opioid (oxycodone) consumption after total knee arthroplasty has revealed considerable analgesic efficacy and opioid sparing effects with dexketoprofen on the first day (between 13 and 24 h), whereas at the second postoperative day (between 25 and 60 h), these effects were more pronounced with diclophenac sodium than with placebo (22).…”
Section: Discussionmentioning
confidence: 99%
“…In many studies, diclophenac has been shown to have potent inhibitory effect on prostaglandin synthesis (22,25). The better analgesic action of diclophenac after 24 h, when compared to lornoxicam and ketoprofen, supports the assumption that diclophenac may also act by different mechanisms other than peripheral inhibition of prostaglandin synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized studies have demonstrated the effectiveness of conventional, non-steroidal antiphlogistics and non-opioid analgesics, such as paracetamol for postoperative pain control (Lohom et al 2002;Peduto et al 1998;Silvanto et al 2002). For high intensity pain these can be combined with strong opioids in multimodal analgesic therapy (Simanski 2008).…”
Section: Accompanying Measures During Inpatient Stay J Pain Managementmentioning
confidence: 99%